Virus-Induced Type I Interferon Deteriorates Control of Systemic Pseudomonas Aeruginosa Infection - Katja Merches (Cellular Physiology and Biochemistry, 2015)
Background: Type I interferon (IFN-I) predisposes to bacterial superinfections, an important problem during viral infection or treatment with interferon-alpha (IFN-α). IFN-I-induced neutropenia is one reason for the impaired bacterial control; however there is evidence that more frequent bacterial infections during IFN-α-treatment occur independently of neutropenia. Methods: We analyzed in a mouse model, whether Pseudomonas aeruginosa control is influenced by co-infection with the lymphocytic choriomeningitis virus (LCMV). Bacterial titers, numbers of neutrophils and the gene-expression of liver-lysozyme-2 were determined during a 24 hours systemic infection with P. aeruginosa in wild-type and Ifnar-/- mice under the influence of LCMV or poly(I:C). Results: Virus-induced IFN-I impaired the control of Pseudomonas aeruginosa. This was associated with neutropenia and loss of lysozyme-2-expression in the liver, which had captured P. aeruginosa. A lower release of IFN-I by poly(I:C)-injection also impaired the bacterial control in the liver and reduced the expression of liver-lysozyme-2. Low concentration of IFN-I after infection with a virulent strain of P. aeruginosa alone impaired the bacterial control and reduced lysozyme-2-expression in the liver as well. Conclusion: We found that during systemic infection with P. aeruginosa Kupffer cells quickly controlled the bacteria in cooperation with neutrophils. Upon LCMV-infection this cooperation was disturbed.